Acceptance of a propofol and remifentanil infusion dosing algorithm to optimize postoperative emergence and analgesia. - Tams, Carl; Johnson, Ken; Seubert, Christoph (Journal of Clinical Monitoring & Computing, 2019)
We implemented a pharmacokinetic/pharmacodynamic (PK/PD) based optimization algorithm recommending intraoperative Remifentanil and Propofol infusion rates to minimize time to emergence and maximize the duration of analgesia in a clinical setting. This feasibility study tested the clinical acceptance of the optimization algorithm's recommendations during scoliosis surgical repair for 14 patients. Anesthesiologist accepted 359/394 (91%) of the recommendations given on the basis of the optimization algorithm. While following the optimization's recommendations the anesthesiologist decreased Propofol infusions from an average of 164-135 mcg/kg/min [p = 0.002] and increased Remifentanil infusions from an average of 0.22-0.30 mcg/kg/min [p = 0.004]. The anesthesiologists appeared to accept and follow the recommendations from a PK/PD based optimization algorithm.